REPRESENTASI POLISI PENGAYOM MASYARAKAT DALAM PROGRAM REALITY SHOW 86 NET. (Analisis Semiotika Roland Barthes) - Ritonga, Muhammad Yusri; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The police can be defined as a civilian public which regulate rules and laws. Police in Indonesia recorded which have many kinds of development from the beginning of independence until today. But in real, society actually asses Police always do slow actions. Furthermore, some cases related to motorcycle crime in different areas that disturb the society. Polri certainly realized that the importance of improve their ability to persuade society, one of them through 86 program on Net. This research aims to determine the meaning of denotation, connotation, and myths on reality show 86 program, knowing representation of police to persuade society which is presented on reality show 86 program.This research uses qualitative research with approach of Roland Barthes semiotics analysis. The Subject in this research is scene on Reality show 86 program of NET production which cooperates with the Indonesian National Police. The data collection techniques through documentation and literature study. To achieve validity of data in this research, researcher uses triangulation technique.The results of this research showed that there are three corresponding meanings in Roland Barthes semiotics. The meaning of denotation on reality show 86 NET such as police behaviors on their duties in the society environment to eradicating motorcycle crime. The meaning of connotations on reality show programs in the form of actions conducted by the police to persuade society in facing many kind of problems that caused by motorcycle crime. The meaning of the myths on reality show program after it was published through a review of literature about police persuade society is Police are able to provide security, protection to society and unlike imagined that police only exist when criminality appear such as motorcycle crime and do not prevent criminality early. The Representation of police to persuade society on reality show 86 program, police protects and helps society, how police make people be safe and secure which include do the best to society and also keeping in mind the prevailing values and norms. Keyword: Representation, Reality Show,Semiotic, Police, Persuade Society.